We are like boats rowing the river of infinity - Vega, Angel (Cinzontle, 2025)
Historical chronicle. This 2024 marks 140 years since the mysterious death of the young Josefina Pannier. In "We are like boats rowing the river of the infinite", a text halfway between historical research, narrative and journalistic chronicle, the author recreates the details of a tragic love developed in ancient San Juan Bautista.